2014
DOI: 10.1037/lat0000009
|View full text |Cite
|
Sign up to set email alerts
|

Does integrated behavioral health care reduce mental health disparities for Latinos? Initial findings.

Abstract: Integrated behavioral health care (IBHC) is a model of mental health care service delivery that seeks to reduce stigma and service utilization barriers by embedding mental health professionals into the primary care team. This study explored whether IBHC service referrals, utilization, and outcomes were comparable for Latinos and non-Latino White primary care patients. Data for the current study were collected from 793 consecutive patients (63.8% Latino; M age = 29.02 years [SD = 17.96]; 35.1% under 18 years; 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(87 citation statements)
references
References 46 publications
3
84
0
Order By: Relevance
“…4,56,57 The preoperative gallstone nomogram developed by Parmar et al 57 is a useful tool for predicting risk of recurrent gallstone complications and can help surgeons weigh the risk of nonoperative intervention against the risk of recurrence.…”
Section: Original Research and Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…4,56,57 The preoperative gallstone nomogram developed by Parmar et al 57 is a useful tool for predicting risk of recurrent gallstone complications and can help surgeons weigh the risk of nonoperative intervention against the risk of recurrence.…”
Section: Original Research and Contributionsmentioning
confidence: 99%
“…54 Although plentiful research has revealed the positive impact of addressing behavioral health issues in primary care settings and empirical evidence shows that integrated care can reduce health disparities, relatively little attention has focused on the unique needs of culturally diverse groups such as African Americans. 42,[55][56][57] A 2016 literature review concluded that "Evidence is lacking about the effectiveness of integrated care offered in a culturally and linguistically competent, patient-centered framework that adequately addresses key concerns and barriers that affect populations at great risk for marginal health." 58 To address this evidence gap, Project THRIVE (Towards Health Recovery and Vital Engagement) offers a promising approach.…”
Section: Integrated Care Models In Culturally Diverse Populationsmentioning
confidence: 99%
“…Previous studies have documented successful interventions among Latino patients using coordinated care, co-located care, and integrated care approaches. Integrated care interventions in these studies were associated with significant improvements in mental health symptoms and functional impairment (Bridges et al, 2014). In addition, our finding may support the development of policies that are informed by differential risk across ethnic groups.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of psychological services into primary care offices has been shown to improve patient outcomes such as depression, anxiety, smoking cessation, and weight loss (Sadock, Auerbach, Rybarczyk, & Aggarwal, ). The integrated behavioral health (IBH) model improves access to care in multiple ways including closing the referral gap found in lower income populations (Reno Conference on the Integration of Behavioral Health in Primary Care, ; Cummings, O'Donohue, & Cummings, ), reducing mental health disparities seen in underserved minority ethnic groups in the United States (Bridges et al, ) and providing treatment opportunities for the estimated 60% of patients whose primary medical complaint has a significant behavioral component (Sobel, ).…”
Section: Introductionmentioning
confidence: 99%